Chemosensitization of tumors via simultaneous delivery of STAT3 inhibitor and doxorubicin through HPMA copolymer-based nanotherapeutics with pH-sensitive activation - Kovář, M; Šubr, V; Běhalová, K; Studenovský, M; Starenko, D; Kovářová, J; Procházková, P; Etrych, T; Kostka, L (Nanomedicine, 2024)
We synthesized three novel STAT3 inhibitors (S3iD1-S3iD3) possessing oxoheptanoic residue enabling linkage to HPMA copolymer carrier via a pH-sensitive hydrazone bond. HPMA copolymer conjugates bearing doxorubicin (Dox) and our STAT3 inhibitors were synthesized to evaluate the anticancer effect of Dox and STAT3 inhibitor co-delivery into tumors. S3iD1-3 and their copolymer-bound counterparts (P-S3iD1-P-S3iD3) showed considerable in vitro cytostatic activities in five mouse and human cancer cell lines with IC50 ~0.6-7.9 μM and 0.7-10.9 μM, respectively. S3iD2 and S3iD3 were confirmed to inhibit the STAT3 signaling pathway. The combination of HPMA copolymer-bound Dox (P-Dox) and P-S3iD3 at the dosage showing negligible toxicity demonstrated significant antitumor activity in B16F10 melanoma-bearing mice and completely cured 2 out of 15 mice. P-Dox alone had a significantly lower therapeutic activity with no completely cured mice. Thus, polymer conjugates bearing STAT3 inhibitors may be used for the chemosensitization of chemorefractory tumors.
Keywords: methakryláty; HPMA copolymer carrier; Humans; pH-sensitive drug release; STAT3 Transcription Factor; doxorubicin; Doxorubicin; lidé; zvířata; myši; STAT3 inhibitor; Mice; transkripční faktor STAT3; Polymethacrylic Acids; Neoplasms; Hydrogen-Ion Concentration; nádory; Animals; kyseliny polymethakrylové; Methacrylates; koncentrace vodíkových iontů